Alkyl dehydrogenation in iridium tri-cyclopentyl phosphines - Moret, S; Dallanegra, R; Chaplin, AB; Douglas, T; Hiney, R; Weller, A (2010)
The iridium cyclooctadiene complex incorporating a tricyclopentyl phosphine ligand (PCyp3), Ir(η2:η2-C8H12)(PCyp3)Cl, has been prepared. Removal of the chloride from this complex using Na [BArF4] [ArF = C6 H3 (CF3)2] in CH2Cl2/arene solvent results in dehydrogenation (C-H activation followed by β-H transfer) of one of the alkyl phosphine rings and formation of the complexes [Ir (η6 - C6 H5 X) {PCyp2 (η2 - C5 H7)}] [BArF4] (X = H, F) which contain a hybrid phosphine-alkene ligand. These complexes are formed alongside another product (5-20% yield) that has been identified as [Ir (η2 : η2 - C8 H12) {PCyp2 (η2 - C5 H7)}] [BArF4], which can be prepared in high yield by an alternative, and slightly modified, route. This complex is with a minor isomer that has been tentatively identified as [Ir (η2 : η3 - C8 H11) (H) {PCyp2 (η2 - C5 H7)}] [BArF4], which results from allylic C-H activation of cyclooctadiene. Addition of H2 to [Ir (η2 : η2 - C8 H12) {PCyp2 (η2 - C5 H7)}] [BArF4] and its isomer in arene solvent (C6H5X, X = F, H) forms the dihydrido η6-arene Ir(III) complexes [Ir (H)2 (η6 - C6 H5 X) (PCyp3)] [BArF4]. In contrast, hydrogenation in CH2Cl2 alone results in the formation of Ir (H)2 (PCyp3) {η6 - (C6 H3 (CF3)2) BArF3} in which the [BArF4]- anion is now acting as a ligand through one of its aryl rings. The fluorobenzene complex [Ir (H)2 (η6 - C6 H5 F) (PCyp3)] [BArF4] can be cleanly converted to [Ir (η6 - C6 H5 F) {PCyp2 (η2 - C5 H7)}] [BArF4] by addition of the hydrogen acceptor tert-butylethene (tbe). © 2009 Elsevier B.V. All rights reserved.